Distribution of Constitutional Funds and Rural Credit in Brazilian Midwest Region - Palheta Borges, Raysa; Rodrigues, Marcos (Organizations and Markets in Emerging Economies, 2025)
Access to credit in agriculture is an important mechanism for increasing farms’ technological level and productivity, while the Fundo Constitucional do Centro-Oeste (FCO) policy also includes a reduction in regional disparities. In this study, we aimed to investigate whether the FCO resources in rural credit are increasing access to rural credit by municipalities in the Brazilian Midwest region. This study covers a panel data of 467 municipalities from 1995 to 2022. To measure credit distribution, we employed inequality indices and an OLS regression to determine the main factors affecting credit demand. The results demonstrated a major concentration of resources, including FCO, in more developed regions where consolidated grain production is predominant. A slight tendency toward diffusing resources was observed, mainly in livestock production financial resources. Structural and institutional constraints in more backward municipalities are responsible for the huge gap in total credit obtained yearly, which the FCO policy is unable to completely surpass, limiting the fund’s intention to promote regional development. This study confirms that the FCO policy for the agricultural sector is market-oriented, funding mainly grains and cattle ranching, which occur more frequently in developed municipalities. We demonstrated that few changes have occurred to transform this pattern over the decades, reducing the effectiveness of this policy.
Keywords: Credit Constraints; Inequality Index; Rural Development; Spatial Data